NOUN DERIVATION OF THE TYPICAL MINAHASA FOOD AND BEVERAGE NAMES - Pamantung, Rina P; Beratha, N.L. Sutjiati; Sutjaja, IGM; Mahyuni, Mahyuni (e-Journal of Linguistics; Vol. 9 Januari 2015 No. 1)
Derivation of the name of typical Minahasa food and beverage is a change or replacement of the word class of verbs, adverbs, and adjectives into nouns. It occurs through the process of compounding, affixation, and reduplication. Free morpheme which appears is ransak , tei, tu'tu, tape, segor, sende ', rica, fresh, rukus . Conversely, some morphemes or bound forms (affixes) are the prefix /pe-/,/wa-/, and / ko- / ; infix /- in -/ ; suffix /-en /, and confixes /-in- + -an / and  / ka- + -an / . Prefixes /pe-/, / wa -/, and / ko -/ ; infix /- in- / ; sufi x-en/, andconfixes /-in- + -an / occur in the formation of derivational words of  food, while  drinks contain two morphemes (affixes), the infix / -in- / and confix (ka + -an). Thus, the derivation of the typical Minahasa food naming is called derivational affixes such as derivational prefix, infix, and confix. Meanwhile, derivational infix, and confix occur in a typical Minahasa drink. Empty derivation is not found in the typical Minahasa food and beverage since a single form, for example, pangi, sa’ut, paniki, kawok, dan sopi have a meaning that does not change the word class. In addition, the characteristics of the structure of itscompounding: root + base (base + roots), that have a sense of the endocentric and exocentric compound words. Endocentric ompounding is the most frequent.
Keywords: derivation, affixation, compounding, reduplication, endocentric and exocentric